2020
DOI: 10.3839/jabc.2020.023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Melissa officinalis L. leaf extract on lipid accumulation by modulating specific adipogenic gene transcription factors in 3T3-L1 adipocytes

Abstract: The objective of this study was to investigate the effects of a hypodermic injectable solution comprised of an LPM LB meso solution containing Melissa officinalis L. leaf extract (LPM) on the lipogenesis in the 3T3-L1 cells line. The lipid accumulation measured by oil red o staining in the 3T3-L1 adipocytes treated with LPM, which was reduced in a dose dependent manner and showed 91.7 to 62.9% compared to control group. Its effectiveness with a 50% solution was significantly higher than the hydroxycitric acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…The leaf extract from Melissa officinalis reduces the mRNA levels of genes involved in lipogenesis, such as the fatty acid synthase (FAS), stearoyl-CoA desaturase 1 (SCD1), and sterol regulatory element-binding protein 1c (SREBP-1c) [ 77 ]. The extract of M. officinalis acts via the C/EBPα and the PPAR pathway [ 78 ]. The extract ALS-L1023 confirmed that the effects of nutraceuticals present in this herb reduce weight gain.…”
Section: Resultsmentioning
confidence: 99%
“…The leaf extract from Melissa officinalis reduces the mRNA levels of genes involved in lipogenesis, such as the fatty acid synthase (FAS), stearoyl-CoA desaturase 1 (SCD1), and sterol regulatory element-binding protein 1c (SREBP-1c) [ 77 ]. The extract of M. officinalis acts via the C/EBPα and the PPAR pathway [ 78 ]. The extract ALS-L1023 confirmed that the effects of nutraceuticals present in this herb reduce weight gain.…”
Section: Resultsmentioning
confidence: 99%